Netters anatomy coloring book - Hansen, John T.
Identical to paperback (ISBN 9780323187985) but in a convenient spiral-bound format! 2015 BMA Medical Book Awards Highly Commended in Basic and Clinical Sciences Category! Learn and master anatomy with ease, while having fun, through the unique approach of Netter's Anatomy Coloring Book, 2nd Edition. You can trace arteries, veins, and nerves through their courses and bifurcations...reinforce your understanding of muscle origins and insertions from multiple views and dissection layers...and develop a better understanding of the integration of individual organs in the workings of each body system throughout the human form. Whether you are taking an anatomy course or just curious about how the body works, let the art of Netter guide you!